Tuberculosis in patients with chronic kidney disease: atypical presentation and diagnostic dilemma - Pradhan, Ravi R. (Journal of Chitwan Medical College, 2018)
Tuberculosis (TB) is a serious public health problem, and more common in developing countries like Nepal. Worldwide, it is the second most frequent cause of death from infectious disease. Patient with chronic kidney disease (CKD) under maintenance dialysis are more likely to develop TB compared to general population. Given the increasing prevalence of CKD in TB endemic areas, a merging of CKD and TB epidemics could have significant public health implications, especially in low- to middle-income countries like Nepal. Because of increased frequency of extra-pulmonary tuberculosis in patient with CKD, the clinical presentation is atypical and leads to diagnostic dilemma.